Composition, distribution, and biodiversity of zooplanktons in tropical lentic ecosystems with different environmental conditions - Ahmad Dini Umi, Wahidah; M. Yusoff, Fatimah; Balia Yusof, Zetty Norhana; Mohamed Ramli, Norulhuda (Multidisciplinary Digital Publishing Institute, 2024)
A study was conducted to evaluate zooplankton species composition, abundance, and diversity in both natural and artificial lakes with varying trophic levels and to determine the relationship between zooplankton community structure and lake environmental conditions. This study hypothesized that correlations exist between zooplankton community structures and environmental parameters associated with eutrophication in natural and man-made lakes. Sampling was conducted across 16 distinct freshwater lentic ecosystems in Malaysia, including natural lakes/swamps, reservoirs, constructed lakes/ponds, and old mining lakes, spanning a range of trophic levels from mesotrophic to hypereutrophic conditions. Physicochemical parameters were measured in situ, while water and zooplankton samples were collected for nutrient analyses, as well as for zooplankton identification and enumeration. Throughout the study, a total of 58 zooplankton species, consisting of 36 species of rotifers, 12 species of cladocerans, and 10 species of copepods. The highest zooplankton density (365.7 ± 13.7 ind. L-1) was recorded in constructed lakes/ponds, while the lowest density was recorded in natural shallow lakes/swamps (200.5 ± 25.5 ind. L−1). On the other hand, significantly higher (p < 0.05) mean species diversity was observed in natural lakes/swamps (H’ = 2.2 ± 0.0), whereas the lowest diversity was in old mining lakes (H’ = 1.5 ± 0.1). The similarity percentage (SIMPER) analysis and canonical correspondence analysis (CCA) scores indicated that Polyarthra vulgaris and Chydorus ventricosus were the discriminating species in natural shallow lakes/swamps associated with high water transparency. Meanwhile, the small-sized cladocerans (Ceriodaphnia cornuta) and rotifers (Keratella spp., Brachionus spp. and Trichocerca spp.). were the most discriminating species in lakes with high turbidity, nutrients, and chlorophyll a concentrations which are the main features of reservoirs and constructed lakes/ponds. Low density and diversity in old mining lakes were due to a low species number and the dominance of two species, Lophocharis curvata (38.8 %) and Ptygura libera (39.7 %). Overall, the high dominance of a specific zooplankton species resulted in lower biodiversity in artificial ecosystem compared to natural ecosystem. This study elucidated zooplankton community structure in lakes was significantly influenced by the environmental conditions related to the lake trophic status.